A STATE-LEVEL EXAMINATION OF RURAL POVERTY IN INDIA FROM 1983-1994 - Sumir Meghani (2003)
This paper examines rural poverty in fifteen Indian states using poverty estimates derived from seven National Sample Survey (NSS) rounds conducted between 1983 and 1994. It distinguishes between farm and nonfarm growth, focusing on the factors that drive the former. The conclusions are that sustained increases in agricultural productivity are critical to reducing rural poverty. When combined with strong human development, in the form of increased literacy, its pro-poor effect is strengthened. The absence of a significant poverty reduction during the last decade may be reflected by a slowdown in the primary sector, especially within India's poorest states.